Chapter 10 Policy transfer and its limits Authorised cartels in twentieth-century Japan - Ohata, Takahiro (Taylor & Francis, 2018)
Cartels, trusts and agreements to reduce competition between firms have existed for centuries, but became particularly prevalent toward the end of the 19th century. In the mid-20th century governments began to use so called 'cartel registers' to monitor and regulate their behaviour. This book provides cases studies from more than a dozen countries to examine the emergence, application and eventual decline of this form of regulation.